The acute cardiorespiratory and cerebrovascular response to resistance exercise - Perry, B. G.; Lucas, S. J. (Sports Medicine - Open, 2021)
Resistance exercise (RE) is a popular modality for the general population and athletes alike, due to the numerous benefits of regular participation. The acute response to dynamic RE is characterised by temporary and bidirectional physiological extremes, not typically seen in continuous aerobic exercise (e.g. cycling) and headlined by phasic perturbations in blood pressure that challenge cerebral blood flow (CBF) regulation. Cerebral autoregulation has been heavily scrutinised over the last decade with new data challenging the effectiveness of this intrinsic flow regulating mechanism, particularly to abrupt changes in blood pressure over the course of seconds (i.e. dynamic cerebral autoregulation), like those observed during RE. Acutely, RE can challenge CBF regulation, resulting in adverse responses (e.g. syncope). Compared with aerobic exercise, RE is relatively understudied, particularly high-intensity dynamic RE with a concurrent Valsalva manoeuvre (VM). However, the VM alone challenges CBF regulation and generates additional complexity when trying to dissociate the mechanisms underpinning the circulatory response to RE. Given the disparate circulatory response between aerobic and RE, primarily the blood pressure profiles, regulation of CBF is ostensibly different. In this review, we summarise current literature and highlight the acute physiological responses to RE, with a focus on the cerebral circulation.